2022
DOI: 10.4236/ojpsych.2022.124022
|View full text |Cite
|
Sign up to set email alerts
|

Refugee Stigma and Its Association with Depression Symptom Severity: Findings from Urban Refugees Living in Mbarara City, Southwestern Uganda

Abstract: Introduction: Refugees in urban areas often face acculturation challenges, stigma, and stereotypes that impact their mental well-being. The aim of the present study was to examine the prevalence of stigma and its association with depressive symptoms among urban refugees living in Mbarara city, southwestern Uganda. Methods: This cross-sectional study used snowball sampling and interviewed 343 refugees residing in Mbarara city, southwestern Uganda. The Discrimination and Stigma Scale was used to assess stigma, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, it has yet to be demonstrated whether there is a clear gender difference in AUD, thus indicating that future studies should investigate the relative effects of AUD between genders. A previous study reported no significant gender difference for the severity of alcohol use among urban refugees 47 . However, other studies reported that females with AUD might suffer from more alcohol‐induced damage than males with AUD 48 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, it has yet to be demonstrated whether there is a clear gender difference in AUD, thus indicating that future studies should investigate the relative effects of AUD between genders. A previous study reported no significant gender difference for the severity of alcohol use among urban refugees 47 . However, other studies reported that females with AUD might suffer from more alcohol‐induced damage than males with AUD 48 .…”
Section: Discussionmentioning
confidence: 88%
“…A previous study reported no significant gender difference for the severity of alcohol use among urban refugees. 47 However, other studies reported that females with AUD might suffer from more alcohol-induced damage than males with AUD. 48 Future studies should incorporate females with AUD to specifically investigate whether there is a gender difference in terms of functional connections and AUD.…”
Section: Correlation Resultsmentioning
confidence: 97%
“…Mbarara City is located in southwestern Uganda (Bahati et al, 2022). It is made up of Kamukuzi Division, Kakoba Division, Biharwe Division, Nyamitanga Division, Nyakayojo Division, and Kakiika Division.…”
Section: Study Areamentioning
confidence: 99%